Pengaruh Teknik Storyboard terhadap Kemampuan Menulis Teks Cerita Pendek Siswa SMK Tritech Informatika Medan - Nisa Hafzhiyah Hasibuan; Faridah Faridah; Rina Devianty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the low ability to write short stories in students, which is thought to be caused by the use of learning methods and media that are less varied and have not been able to stimulate students' imagination and creativity optimally. To overcome this problem, the application of innovative learning strategies is needed, one of which is the use of storyboard techniques. The purpose of this study was to determine the effect of storyboard techniques on the ability to write short stories of class X students of SMK Tritech Informatika Medan. The method used in this study is a quantitative method with a quasi-experimental design, specifically the Pretest-Posttest Control Group Design. The sample in this study amounted to 42 students who were divided into two groups, namely the experimental group who were given treatment using the storyboard technique and the control group who used conventional methods. Data collection techniques were carried out through observation, interviews, short story writing tests, and documentation. The data obtained were analyzed using normality tests, homogeneity tests, and t-tests (independent samples t-test). The results showed that there was a significant difference between the posttest scores of the experimental group and the control group. The experimental group experienced an average score increase of 18.81 points, while the control group only increased by 9.76 points. The t-test results showed a t-value of 2.677 and a significance level of p = 0.011 (p < 0.05), indicating that the storyboard technique had a significant effect on students' short story writing skills. Therefore, it can be concluded that the use of the storyboard technique is effective in improving students' creative writing skills. The implication of this finding is that the storyboard technique can be used as an alternative, creative and innovative learning strategy in writing instruction at the Vocational High School (SMK) level.